Taxation and Economic Stability - Gilbert, Donald W. (Quarterly Journal of Economics, 1942)
Introduction: the problem, 406. — General character of cyclical tax policy: in booms, 409; in recessions, 411. — Certain measurable effects of federal taxation, 412. — Taxes tending to reduce consumer spending, 414. — The individual income tax, 415. — Estate and gift taxes, 417. — Corporation taxes, 417. — Other taxes, 418. — Implications of the federal tax ratio, 419. — State and local revenues, 423. — Further objection to the ratio, 425. — Importance of qualitative considerations, 426. — Alleged counterbalancing effects of public expenditures, 427. — Conclusions, 427.